Hubungan Pekerjaan, Genetik, dan Usia Klien Dengan Kejadian Hipertensi di Puskesmas Petaling Kabupaten Banyuasin Tahun 2022 - Irwadi I; Dedi Fatrida; Yenni Elfira (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Hypertension is an increase in systolic pressure greater than or equal to 160 mmHg or diastolic pressure equal to or greater 95 mmHg (Kodim Nasrin, 2003). High blood pressure is one risk factor for stroke, heart attack, heart failure and arterial aneurysm, and is a major cause of chronic heart failure. The purpose of this study was to determine the relationship between employment, genetic and age with the incidence of hypertension in Petaling District Health Center Banyuasin 2022. Samples were obtained using the method of accidental sampling with total sample of 61 respondents, by using accidental sampling technique. Data analysis was carried out by two stages of data analysis of univariate and bivariate analysis with Chi-Square test statistics program SPSS. Results of univariate analysis showed that respondents who suffer from hypertension as much as 38 respondents (62.3%), while those not suffering from hypertension were 23 respondents (37.7%). From the results of the bivariate analysis found no significant relationship between the job with hypertension in which p-value = 0.006 and significant relationship between genetic with hypertension in which p-value = 0.011. From the results of the bivariate analysis found no significant relationship between age with hypertension in which p-value = 0.006. Based on these results, it can be concluded that there is a significant relationship between employment, genetic and age with hypertension in Petaling district health centers Banyuasin 2022.